Sarcopenia as a predictor of mortality in centenarians: insights from a prospective cohort study - Yun Tang; Hongyan Lin; Meijuan Chen; Yuanyuan Zhong; Xiaochu Wu; Li Wang (BMC Geriatrics)
Abstract Background & aims Centenarians represent a unique population where predictors of mortality are understudied.Studies have shown that sarcopenia is associated with adverse health outcomes and premature death in elderly patients. The aim of our study was to explore the association between sarcopenia and centenarian mortality. Methods Our study is a prospective cohort study. Muscle mass was measured using bioelectrical impedance analysis (BIA), and the relative skeletal muscle index (RSMI) was adjusted for height to reduce individual differences. Sarcopenia is defined according to the Asian Sarcopenia Working Group’s (AWGS)2019 updated diagnostic criteria for sarcopenia, it introduces the concept of “possible sarcopenia”, defined as the presence of only low muscular strength or low physical performance, specifically for primary health care or community health promotion to enable earlier lifestyle interventions. The survival time of centenarians with and without sarcopenia was compared using the Kaplan-Meier method, and the hazard ratio (HR) and 95% confidence interval (95% CI) for mortality were determined using the Cox proportional hazards regression model. Results A total of 98 centenarians were included in this study, with an average age of (102.2 ± 1.8) years. The prevalence of sarcopenia was 20.4%. The Cox proportional hazards model analysis showed that after adjusting for confounding factors, the risk of death was increased by 3.64 times in the sarcopenia group (HR = 4.64, 95% CI: 2.48–8.66). Conclusion Sarcopenia can serves as a significant predictor of long-term mortality in centenarians and functions as an important independent predictor. Trial registration The trial was registered at the Chinese Clinical Trial Center on 17-01-2019. Trial registration numbers 2018 − 463; ChiCTR1900020754.